Analisa Kelayakan Taxiway Light (Studi Kasus Bandara Rendani Manokwari): Analysis of Feasibility for Taxiway Light (Case Study in Rendani Airport of Manokwari) - Raja H. Tampubolon; Henny A. B. Lesnussa; Abdul Z. Patiran (Universitas Papua, 2022)
Taxiway Light is a road that connects between the apron and the runway. Its existence is very important because with the taxiway light, the aircraft can go to an apron safely without disturbing other aircraft. CCR or Constant Current Regulator as a component, its functions to regulates a current fixed and constant in taxiway light with the lighting level divided into five levels, namely step 1 to step 5. The electrical system on the taxiway light is assembled and installed in series with the intention that if one of the circuits is extinguished, the other system is still running. The electrical system on the taxiway light uses the CCR components to produce a constant current. This research used the case study method. The existing load data on step1 is 3,727 Watts, step 2 is 4,495 Watts, step 3 is 5,450 Watts, step 4 is 6,896 Watts, step 5 is 8,723 Watts and step 1for load calculation data is 3,527 Watts, step 2 is 4,488 Watts, step 3 is 5,438 Watts, step 4 is 6,864 Watts, step 5 is 8,712 Watts which means that the results of the comparison at Rendani Airport are feasible because the existing load data is greater than the load data of the calculation results.